Beliefs, knowledge and the impact of COVID19 on menopause therapies in Spanish women: COMEM-treatment study - Laura Baquedano; Andrea Espiau; María Fasero; Silvia Ortega; Isabel Ramirez; Nicolás Mendoza; The COMEM Study Spanish investigators (BMC, 2020)
Abstract Objective To study what women think about menopause treatments and assess their knowledge about them. To analyze adherence to treatment during COVID-19 confinement as a secondary objective. Methods A multi-center cross-sectional observational study was conducted using a survey of 2500 women between January and June 2019. This was administered following a non-probability sampling procedure including women between 35 and 75 years. An extension study was conducted during the coronavirus pandemic, between March and June 2020. Results The responses of 2355 surveyed women were analyzed. Of this sample, 42% knew about menopause hormone therapy (MHT). The most frequently identified indication was the treatment of hot flashes (65.6%). The MHT risks most frequently perceived were weight gain (24.2%) and breast cancer (21.7%); the main reason for rejecting MHT was a lack of information (96.1%). Comparative analyses were conducted according to age, menopausal status, type of menopause, place of residence, type of health care and level of education. During the coronavirus confinement period, 85 women using MHT were located, of which 84.7% continued it. Conclusions Women hold certain false beliefs about menopause, and their knowledge of the available treatments is somewhat limited. Adherence to MHT during the COVID-19 confinement in Spain has been high.